Bonding paste and method for manufacturing bonded body

The bonding paste with copper particles, a solvent, and a phosphate ester additive addresses the oxidation issue of copper paste in non-reducing atmospheres, maintaining the strength of the bonding layer and ensuring reliable joint integrity.

JP7666011B2Active Publication Date: 2025-04-22MITSUBISHI MATERIALS CORP
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021026575
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-02-22
Publication Date
2025-04-22
Estimated Expiration
2041-02-22

AI Technical Summary

Technical Problem

Copper paste is prone to oxidation in non-reducing atmospheres, leading to a decrease in the strength of the bonding layer when used for joining components.

Method used

A bonding paste containing copper particles, a solvent, and a phosphate ester additive, with the phosphate ester content ranging from 0.5% to 3.0% by mass, is used to form a bonding layer that suppresses oxidation and maintains strength in non-reducing atmospheres.

Benefits of technology

The use of the bonding paste with phosphate ester effectively suppresses the decrease in strength of the bonding layer even when bonded in a non-reducing atmosphere, ensuring reliable joint integrity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007666011000002
    Figure 0007666011000002
  • Figure 0007666011000003
    Figure 0007666011000003
  • Figure 0007666011000001
    Figure 0007666011000001
Patent Text Reader

Abstract

To prevent joint strength of members from deteriorating even when the members are joined together in a nonreducing atmosphere.SOLUTION: A paste for joining 10 has copper particles 12, a solvent 14, and an additive 16 composed of a phosphoester. In the paste for joining 10, the content of the additive 16 is 0.5% or more and 3.0% or less in mass ratio to the total of the paste for joining 10.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a bonding paste and a method for producing a bonded body. [Background technology]

[0002] When two or more parts are joined, a joining material is generally used. For example, Patent Document 1 describes the use of solder as a joining material. In addition, in recent years, the heat resistance of non-joined objects such as semiconductor elements has improved, and they are increasingly used in high-temperature environments such as the engine room of an automobile, so that, for example, as shown in Patent Document 2, silver paste may be used as a joining material. Silver paste can be sintered under relatively low-temperature conditions, and the melting point of the joining layer formed after sintering is equivalent to that of silver. For this reason, the joining layer made of the sintered body of this silver paste has excellent heat resistance and can be used stably in high-temperature environments and large current applications. On the other hand, from the viewpoint of material cost, for example, as shown in Patent Document 3, copper paste may be used as a joining material. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2004-172378 A [Patent Document 2] Patent No. 6531547 [Patent Document 3] JP 2019-67515 A Summary of the Invention [Problem to be solved by the invention]

[0004] However, copper is easily oxidized, and when components are bonded together using a copper paste in a non-reducing atmosphere, the strength of the bonding layer may decrease.

[0005] The present invention has been made in consideration of the above, and aims to provide a joining paste that can suppress a decrease in strength even when joining is performed in a non-reducing atmosphere, and a method for manufacturing a joined body. [Means for solving the problem]

[0006] In order to solve the above problems, the bonding paste of the present disclosure is a bonding paste containing copper particles, a solvent, and an additive consisting of a phosphate ester, and the content of the additive is 0.5% or more and 3.0% or less by mass ratio with respect to the entire bonding paste.

[0007] In order to solve the above problems, the manufacturing method of the bonded body of the present disclosure manufactures a bonded body by bonding a first member and a second member together using the bonding paste as a bonding layer. Effect of the Invention

[0008] According to the present invention, it is possible to suppress a decrease in strength even when bonding is performed in a non-reducing atmosphere. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 is a schematic diagram of the bonding paste according to this embodiment. [Diagram 2] FIG. 2 is a schematic diagram of the bonded body according to this embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The present invention will be described in detail below with reference to the drawings. Note that the present invention is not limited to the following modes for carrying out the invention (hereinafter, referred to as embodiments). Furthermore, the components in the following embodiments include those that a person skilled in the art can easily imagine, those that are substantially the same, and those that are within the so-called equivalent range. Furthermore, the components disclosed in the following embodiments can be appropriately combined. Also, the numerical values ​​include the range of rounding.

[0011] Fig. 1 is a schematic diagram of a bonding paste according to the present embodiment. The bonding paste according to the present embodiment is used to bond members together. As shown in Fig. 1, a bonding paste 10 according to the present embodiment contains copper particles 12, a solvent 14, and an additive 16. Note that Fig. 1 is a schematic diagram, and the shape of the actual bonding paste 10 is not limited to that shown in Fig. 1.

[0012] (Copper particles) The copper particles 12 preferably have a BET diameter of 50 nm or more and 300 nm or less. The BET diameter is a particle diameter calculated from the BET specific surface area and true density of the copper particles obtained by the BET method, assuming that the copper particles 12 are true spheres or cubes. Specifically, it can be obtained by the method described in the examples below.

[0013] If the BET diameter of the copper particles 12 is 50 nm or more, it is difficult to form strong aggregates. Therefore, the surface of the copper particles 12 can be uniformly coated with the solvent 14. On the other hand, if the BET diameter of the copper particles 12 is 300 nm or less, the reaction area is large and the sintering property by heating is high, so that a strong bonding layer can be formed. The BET diameter of the copper particles 12 is preferably in the range of 80 nm to 200 nm, and particularly preferably in the range of 80 nm to 170 nm.

[0014] The BET specific surface area of ​​copper particles 12 is 2.0 m 2 / g or more 8.0m 2 It is preferable that the range is 3.5m / g or less. 2 / g or more 8.0m 2 / g or less, and more preferably 4.0m 2 / g or more 8.0m 2 / g or less. The shape of the copper particles 12 is not limited to a spherical shape, and may be a needle shape or a flat plate shape.

[0015] The surfaces of the copper particles 12 are preferably coated with an organic protective film, which is a film of an organic material. By being coated with the organic protective film, oxidation of the copper particles 12 is suppressed, and a decrease in sinterability due to oxidation of the copper particles 12 is further unlikely to occur. The organic protective film coating the copper particles 12 is not formed by the solvent 14, and can be said to be not derived from the solvent 14. It can also be said that the organic protective film coating the copper particles 12 is not a copper oxide film formed by the oxidation of copper.

[0016] The fact that the copper particles 12 are coated with an organic protective film can be confirmed by analyzing the surface of the copper particles 12 using time-of-flight secondary ion mass spectrometry (TOF-SIMS). Therefore, in this embodiment, the copper particles 12 are coated with an organic protective film, and the organic protective film is detected by analyzing the surface of the copper particles 12 using time-of-flight secondary ion mass spectrometry. + C3H3O3 vs. ion detection amount - Ratio of detected ions (C3H3O3 - / Cu + It is preferable that the ratio is 0.001 or more. C3H3O3 - / Cu + The ratio is more preferably in the range of 0.05 to 0.2. Note that the surface of copper particles 12 in this analysis does not refer to the surface of copper particles 12 when the organic protective film is removed from copper particles 12, but refers to the surface of copper particles 12 including the covering organic protective film (i.e., the surface of the organic protective film).

[0017] The copper particles 12 were analyzed by surface analysis using time-of-flight secondary ion mass spectrometry to determine that the copper particles were C3H4O2 - Cu ions and ions of C5 or higher may be detected. + C3H4O2 vs. ion detection amount - Ratio of detected ions (C3H4O2 - / Cu + The ratio is preferably 0.001 or more. + The ratio of the amount of ions detected that are C5 or more to the amount of ions detected (C5 or more ions / Cu + It is preferable that the ratio is less than 0.005.

[0018] C3H3O3 detected by time-of-flight secondary ion mass spectrometry - Ions and C3H4O2 - The C3H3O3 ions and C5 or higher ions originate from the organic protective film that covers the surface of the copper particles 12. - / Cu + Ratio and C3H4O2 - / Cu + When each of the ratios is 0.001 or more, the surface of the copper particles 12 is less likely to be oxidized, and the copper particles 12 are less likely to aggregate. - / Cu + Ratio and C3H4O2 - / Cu + When the ratio is 0.2 or less, the oxidation and aggregation of the copper particles 12 can be suppressed without excessively decreasing the sinterability of the copper particles 12, and further, the generation of decomposition gas of the organic protective film during heating can be suppressed, so that a bonding layer with fewer voids can be formed. - / Cu + Ratio and C3H4O2 - / Cu + The ratio is preferably in the range of 0.08 to 0.16. + If the ratio is 0.005 or more, the particle surface will have a large amount of organic protective film with a relatively high desorption temperature, resulting in insufficient sintering and making it difficult to obtain a strong bonding layer. + Preferably, the ratio is less than 0.003.

[0019] The organic protective film is preferably derived from citric acid. A method for producing copper particles 12 coated with an organic protective film derived from citric acid will be described later. The amount of the organic protective film on the copper particles 12 is preferably in the range of 0.5% by mass to 2.0% by mass, more preferably in the range of 0.8% by mass to 1.8% by mass, and even more preferably in the range of 0.8% by mass to 1.5% by mass, based on 100% by mass of the copper particles. When the amount of the organic protective film is 0.5% by mass or more, the copper particles 12 can be uniformly coated with the organic protective film, and oxidation of the copper particles 12 can be more reliably suppressed. In addition, when the amount of the organic protective film is 2.0% by mass or less, it is possible to suppress the generation of voids in the sintered body (bonding layer) of the copper particles due to gas generated by decomposition of the organic protective film by heating. The amount of the organic protective film can be measured using a commercially available device. For example, the amount of the coating can be measured using a differential thermobalance TG8120-SL (manufactured by RIGAKU Corporation). In this case, for example, copper particles from which moisture has been removed by freeze-drying are used as the sample. Measurements are performed in nitrogen (G2 grade) gas to suppress oxidation of the copper particles, and the temperature rise rate is set to 10°C / min. The weight loss rate when heated from 250°C to 300°C can be defined as the coating amount of the organic protective film. In other words, coating amount = (sample weight after measurement) / (sample weight before measurement) x 100 (wt%). Measurements are performed three times for each copper particle from the same lot, and the arithmetic mean value can be used as the coating amount.

[0020] It is preferable that 50% by mass or more of the organic protective film of the copper particles 12 decomposes when heated for 30 minutes at a temperature of 300° C. in an atmosphere of an inert gas such as argon gas. The organic protective film derived from citric acid generates carbon dioxide gas, nitrogen gas, evaporated acetone gas, and water vapor during decomposition.

[0021] Copper particles 12 coated with an organic protective film derived from citric acid can be produced, for example, as follows. First, an aqueous dispersion of copper citrate is prepared, and a pH adjuster is added to the aqueous dispersion of copper citrate to adjust the pH to 2.0 or more and 7.5 or less. Next, in an inert gas atmosphere, a hydrazine compound capable of reducing copper ions is added as a reducing agent to the aqueous dispersion of copper citrate with a 1.0-fold equivalent or more and 1.2-fold equivalent or less of the copper ion-reducing agent and mixed. The resulting mixture is heated to a temperature of 60° C. or more and 80° C. or less in an inert gas atmosphere and held for 1.5 hours or more and 2.5 hours or less. As a result, the copper ions eluted from the copper citrate are reduced to produce copper particles 12, and an organic protective film derived from citric acid is formed on the surface of the copper particles 12.

[0022] The aqueous dispersion of copper citrate can be prepared by adding powdered copper citrate to pure water such as distilled water or ion-exchanged water to a concentration of 25% by mass or more and 40% by mass or less, and stirring with a stirring blade to uniformly disperse the copper citrate. Examples of pH adjusters include triammonium citrate, ammonium hydrogen citrate, and citric acid. Among these, triammonium citrate is preferred because it is easy to adjust the pH to a mild level. The reason why the pH of the aqueous dispersion of copper citrate is set to 2.0 or more is to increase the elution rate of copper ions eluted from copper citrate, to rapidly advance the generation of copper particles, and to obtain the target fine copper particles 12. The reason why the pH is set to 7.5 or less is to prevent the eluted copper ions from becoming copper hydroxide (II) and to increase the yield of the copper particles 12. The reason why the pH is set to 7.5 or less is to prevent the reducing power of the hydrazine compound from becoming excessively high, and the target copper particles 12 can be easily obtained. The pH of the copper citrate aqueous dispersion is preferably adjusted to within the range of 4 or more and 6 or less.

[0023] The reduction of copper citrate with a hydrazine compound is carried out under an inert gas atmosphere. This is to prevent oxidation of copper ions dissolved in the liquid. Examples of inert gases include nitrogen gas and argon gas. When reducing copper citrate under acidic conditions, hydrazine compounds have the advantages of not producing residues after the reduction reaction, being relatively safe, and being easy to handle. Examples of this hydrazine compound include hydrazine monohydrate, anhydrous hydrazine, hydrazine hydrochloride, and hydrazine sulfate. Among these hydrazine compounds, hydrazine monohydrate and anhydrous hydrazine are preferred because they do not contain components that can become impurities such as sulfur and chlorine.

[0024] Generally, copper produced in an acidic solution with a pH of less than 7 dissolves. However, in this embodiment, a hydrazine compound, which is a reducing agent, is added and mixed with an acidic solution with a pH of less than 7, and copper particles 12 are produced in the resulting mixed solution. As a result, components derived from citric acid produced from copper citrate quickly cover the surfaces of the copper particles 12, suppressing the dissolution of the copper particles 12. It is preferable to keep the temperature of the aqueous dispersion of copper citrate after adjusting the pH at 50° C. or higher and 70° C. or lower to facilitate the progress of the reduction reaction.

[0025] The mixed solution containing the hydrazine compound is heated to a temperature of 60°C to 80°C in an inert gas atmosphere and held for 1.5 to 2.5 hours in order to generate copper particles 12 and to form and coat the surfaces of the generated copper particles 12 with an organic protective film. The reason for holding the mixture under heating in an inert gas atmosphere is to prevent oxidation of the generated copper particles 12. Copper citrate, which is the starting material, usually contains about 35% by mass of copper components. By adding a hydrazine compound, which is a reducing agent, to a copper citrate aqueous dispersion containing this amount of copper components, heating it to the above temperature, and holding it for the above time, the generation of copper particles 12 and the generation of an organic protective film on the surfaces of the copper particles 12 proceed in a well-balanced manner, so that copper particles 12 having a coating amount of the organic protective film in the range of 0.5% by mass to 2.0% by mass can be obtained with respect to 100% by mass of copper particles. If the heating temperature is less than 60°C and the holding time is less than 1.5 hours, the copper citrate may not be completely reduced, the production rate of the copper particles 12 may become too slow, and the amount of the organic protective film covering the copper particles 12 may become excessive. If the heating temperature exceeds 80°C and the holding time exceeds 2.5 hours, the production rate of the copper particles 12 may become too fast, and the amount of the organic protective film covering the copper particles 12 may become too small. The preferred heating temperature is 65°C or higher and 75°C or lower, and the preferred holding time is 2 hours or higher and 2.5 hours or lower.

[0026] The copper particles 12 produced in the mixed liquid are subjected to solid-liquid separation from the mixed liquid under an inert gas atmosphere, for example, using a centrifuge, and then dried by freeze-drying or vacuum drying to obtain copper particles 12 whose surfaces are coated with an organic protective film. Since the copper particles 12 have their surfaces coated with an organic protective film, they are less likely to oxidize even if stored in the air until they are used as the bonding paste 10.

[0027] (solvent) The solvent 14 acts as a binder for the copper particles 12. The solvent 14 is an organic solvent. Any solvent may be used as the solvent 14, and examples thereof include alcohol-based solvents, glycol-based solvents, acetate-based solvents, hydrocarbon-based solvents, and amine-based solvents. Specific examples of alcohol-based solvents include α-terpineol and isopropyl alcohol. Specific examples of glycol-based solvents include ethylene glycol, diethylene glycol, and polyethylene glycol. Specific examples of acetate-based solvents include butyl acetate tolcarbitate. Specific examples of hydrocarbon-based solvents include decane, dodecane, and tetradecane. Specific examples of amine-based solvents include hexylamine, octylamine, and dodecylamine.

[0028] (Additives) The additive 16 is a phosphoric acid ester. Among organic phosphoric acid compounds, esters obtained by dehydration condensation of phosphoric acid and alcohol may be called phosphoric acid esters. The phosphoric acid ester used as the additive 16 preferably has an average molecular weight of 1000 or more and 2000 or less, more preferably 1200 or more and 1800 or less, and even more preferably 1400 or more and 1600 or less. When the average molecular weight of the phosphoric acid ester is 1000 or more, decomposition at room temperature is suppressed and storage stability is improved, and when the average molecular weight is 2000 or less, decomposition and reaction at a target heating temperature (about 200 to 350°C) are possible. The average molecular weight here refers to a weight average molecular weight. The average molecular weight can be measured, for example, by size exclusion chromatography.

[0029] The phosphate ester used in the additive 16 may be any, and examples thereof include laureth-n phosphate, oleth-n phosphate, steareth-n phosphate (n is an integer), etc. One of these may be used as the additive 16, or two or more of them may be used.

[0030] (Joint paste) In this embodiment, the bonding paste 10 preferably does not contain any substances other than the copper particles 12, the solvent 14, and the additive 16 made of phosphate ester, except for unavoidable impurities. However, the bonding paste 10 is not limited thereto, and may contain additives other than the copper particles 12, the solvent 14, and the additive 16 made of phosphate ester.

[0031] The content of the additive 16 in the bonding paste 10 is 0.5% to 3.0%, preferably 0.5% to 2.0%, and more preferably 1.0% to 1.5%, by mass ratio relative to the entire bonding paste 10. When the content of the additive 16 is within this range, oxidation of the copper particles 12 is suppressed, and as a result, a decrease in the strength of the bonding layer when members are bonded together using the bonding paste 10 in a non-reducing atmosphere can be appropriately suppressed.

[0032] The content of the solvent 14 in the bonding paste 10 is preferably 5% to 20%, more preferably 5% to 15%, and even more preferably 8% to 13%, by mass ratio relative to the entire bonding paste 10. When the content of the solvent 14 is within this range, the copper particles 12 can be appropriately dispersed.

[0033] (Method of manufacturing bonding paste) The bonding paste 10 is manufactured by performing a mixing process of mixing the copper particles 12, the solvent 14, and the additive 16. In this mixing process, the copper particles 12, the solvent 14, and the additive 16 are mixed so that the content of the additive 16 is 0.5% or more and 3.0% or less by mass ratio with respect to the entire bonding paste 10. In addition, in the mixing process, the copper particles 12, the solvent 14, and the additive 16 are mixed so that the content of the solvent 14 and the copper particles 12 with respect to the entire bonding paste 10 is also within the above range. In addition, in the mixing process, the copper particles 12, the solvent 14, and the additive 16 may be mixed using a kneading device. As the kneading device, for example, a three-roll mill is used.

[0034] (Method of Manufacturing Joint) FIG. 2 is a schematic diagram of a bonded body according to the present embodiment. As shown in FIG. 2, in the present embodiment, a bonded body 30 is manufactured by bonding a first member 21 and a second member 22 using a bonding paste 10 as a bonding layer 20. The first member 21 and the second member 22 may be any member, and for example, one of the first member 21 and the second base material may be a substrate, and the other may be an electronic component. That is, a semiconductor module in which a substrate and an electronic component are bonded by a bonding layer 20 may be manufactured as the bonded body 30. The substrate is not particularly limited, and examples thereof include an oxygen-free copper plate, a copper molybdenum plate, a high heat dissipation insulating substrate (for example, DCB (Direct Copper Bond)), and a substrate for mounting a semiconductor element such as an LED (Light Emitting Diode) package. Examples of electronic components include semiconductor elements such as IGBTs (Insulated Gate Bipolar Transistors), diodes, Schottky barrier diodes, MOS-FETs (Metal Oxide Semiconductor Field Effect Transistors), thyristors, logic, sensors, analog integrated circuits, LEDs, semiconductor lasers, and oscillators.

[0035] In this manufacturing method, a coating layer forming step is performed in which the bonding paste 10 is applied to at least one surface of the first member 21 and the second member 22 to form a coating layer. The coating method is not particularly limited, and examples thereof include spin coating, metal masking, spray coating, dispenser coating, knife coating, slit coating, inkjet coating, screen printing, offset printing, and die coating. Next, a preheating step is performed at a temperature of 50°C to 150°C for 1 minute to 30 minutes to volatilize the solvent in the paste. Next, a superposition step is performed in which the first member 21 and the second member 22 are superposed with the coating layer interposed therebetween.

[0036] Next, a heating step is performed in which the first member 21 and the second member 22 overlapped with the coating layer interposed therebetween are heated. In the heating step, in a non-reducing atmosphere, at least one of the overlapping first member 21 and the second member 22 is heated at a predetermined temperature for a predetermined time while applying a predetermined pressure to the first member 21 and the second member 22. By performing the heating step, the copper particles 12 in the coating layer are sintered to form a bonding layer 20, and a bonded body 30 in which the first member 21 and the second member 22 are bonded with the bonding layer 20 is manufactured.

[0037] The non-reducing atmosphere in the heating step refers to a state in which a non-reducing gas is filled, and can also be called an inert gas atmosphere in which an inert gas is filled. Examples of the non-reducing gas include nitrogen and rare gases such as argon. For example, in this embodiment, the heating step may be performed in a nitrogen atmosphere with an oxygen concentration of 1000 ppm. By performing the heating step in a non-reducing atmosphere, it is not necessary to use a reducing gas, and the heating step can be easily performed.

[0038] Moreover, the predetermined pressure applied to at least one of the first member 21 and the second member 22 is preferably 0.5 MPa to 10 MPa, more preferably 1 MPa to 5 MPa, and even more preferably 2 MPa to 5 MPa. By applying a pressure in such a relatively low range, the first member 21 and the second member 22 can be appropriately bonded together while suppressing defects in the shape of the bonding layer 20. The pressure is applied in a direction in which the first member 21 and the second member 22 are pressed against each other relatively via the coating layer.

[0039] Moreover, the predetermined temperature, which is the heating temperature in the heating step, is preferably 200° C. or more and 300° C. or less, more preferably 230° C. or more and 300° C. or less, and even more preferably 250° C. or more and 300° C. or less. By setting the heating temperature in such a relatively low range, it is possible to appropriately sinter the copper particles 12 while suppressing defects in the shape of the bonding layer 20.

[0040] In addition, the predetermined time, which is the heating time in the heating step, is preferably from 1 minute to 10 minutes, more preferably from 1 minute to 5 minutes, and even more preferably from 1 minute to 3 minutes. By setting the heating time within this range, the copper particles 12 can be appropriately sintered.

[0041] (Joining layer) As described above, the bonding layer 20 in this embodiment is formed by heating the bonding paste 10 and sintering the copper particles 12. The bonding layer 20 is located between the first member 21 and the second member 22, and bonds the first member 21 and the second member 22. The bonding layer 20 can also be said to be a sintered body of copper. In the bonding layer 20, the sintered density of the copper particles is preferably 80% or more, more preferably 85% or more and 95% or less, and even more preferably 85% or more and 90% or less. When the sintered density is in this range, the bonding layer 20 can ensure electrical conductivity and thermal conductivity. The sintered density refers to the ratio of the volume of the bonding layer 20 excluding the open pores and closed pores to the entire volume of the bonding layer 20 including the open pores and closed pores. The sintered density was calculated by binarizing images of the cross section of the bonding layer randomly taken at a magnification of 30,000 times using an SEM (Scanning Electron Microscope) and dividing the images into particle and pore portions using image processing software (ImageJ, manufactured by the National Institutes of Health, USA), and calculating the sintered density using the following formula. Sintered density (%) = (total area of ​​grains / (total area of ​​grains + total area of ​​voids)) x 100

[0042] The bonding layer 20 contains phosphorus. Here, phosphorus refers to phosphorus as an element, and includes not only simple phosphorus but also phosphorus contained in any compound. The phosphorus content of the bonding layer 20 is preferably 10 ppm or more and 1000 ppm or less, more preferably 50 ppm or more and 500 ppm or less, and even more preferably 100 ppm or more and 500 ppm or less, by mass ratio, relative to the entire bonding layer 20. When the phosphorus content is within this range, the bonding layer 20 is prevented from decreasing in strength even when formed, for example, under a non-reducing atmosphere. The phosphorus content can be measured by ICP-OES (ICP optical emission spectrometer). In this embodiment, the phosphorus contained in the bonding layer 20 is derived from the phosphate ester contained in the bonding paste 10.

[0043] The thickness of the bonding layer 20 is preferably 10 μm to 200 μm, more preferably 20 μm to 150 μm, and even more preferably 50 μm to 100 μm. By having the thickness in this range, the bonding layer 20 can maintain high heat dissipation while mitigating stress caused by the difference in linear expansion coefficient between members due to temperature difference.

[0044] Thus, the bonding layer 20 according to this embodiment is a copper sintered body containing phosphorus, with a sintered density of 80% or more. Since the bonding layer 20 according to this embodiment has a sintered density of 80% or more, a decrease in strength is suppressed. Furthermore, the phosphorus-derived material (phosphate ester in this embodiment) contained in the bonding layer 20 suppresses oxidation of the copper particles 12, and as a result, the bonding layer 20 containing phosphorus is suppressed from decreasing in strength. Note that, as described above, the bonding layer 20 in this embodiment is formed by heating the bonding paste 10, but the bonding layer 20 may be formed by any method as long as it satisfies the above characteristics.

[0045] (effect) As described above, the bonding paste 10 according to the present embodiment contains copper particles 12, a solvent 14, and an additive 16 made of a phosphate ester, and the content of the additive 16 is 0.5% or more and 3.0% or less by mass ratio with respect to the entire bonding paste 10. In the bonding paste 10 according to the present embodiment, the addition of the phosphate ester as an additive suppresses oxidation of the copper particles 12, and as a result, even when members are bonded together in a non-reducing atmosphere, the decrease in strength of the bonding layer can be suppressed.

[0046] Moreover, the manufacturing method of the bonding paste 10 according to the present embodiment includes a step of manufacturing the bonding paste 10 by mixing the copper particles 12, the solvent 14, and the additive 16 so that the content of the additive 16 is 0.5% or more and 3.0% or less by mass ratio with respect to the entire bonding paste 10. According to this manufacturing method, by adding a phosphoric ester as an additive, oxidation of the copper particles 12 is suppressed, and as a result, even when members are bonded to each other in a non-reducing atmosphere, a decrease in the strength of the bonding layer can be suppressed.

[0047] In addition, the method for manufacturing a bonded body according to the present embodiment manufactures a bonded body by bonding a first member and a second member together using the bonding paste 10 as a bonding layer. According to this method, since the bonding paste 10 is used as a bonding layer, a decrease in the strength of the bonding layer can be suppressed even when the members are bonded together in a non-reducing atmosphere.

[0048] (Example) Next, an embodiment will be described.

[0049] Example 1 In Example 1, copper particles with a BET diameter of 153 nm were prepared. The BET diameter was determined by measuring the amount of nitrogen gas adsorbed by the copper particles using a specific surface area measuring device (QUANTACHROME AUTOSORB-1, manufactured by Quantachrome Instruments) and calculating the specific surface area of ​​the copper particles by the BET method. The obtained specific surface area S (m 2 / g) and the density of the copper particles ρ (g / cm 3 ) and the BET diameter was calculated according to the following formula. BET diameter (nm) = 6000 / (ρ(g / cm 3 )×S(m 2 / g)) In Example 1, oleth-10 phosphoric acid was prepared as the phosphoric ester for the additive, and ethylene glycol was prepared as the solvent. In Example 1, the copper particles, the additive, and the solvent were mixed so that the content of the additive was 1 mass %, the content of the solvent was 10 mass %, and the remainder was copper particles, to obtain a bonding paste.

[0050] (Examples 2-10) In Examples 2-10, a joining paste was obtained in the same manner as in Example 1, except that the BET diameter of the copper particles, the type of additive, the type of additive, the additive content, or the solvent content were as shown in Table 1.

[0051] (Comparative Example 1-3) In Comparative Example 1-3, a bonding paste was obtained in the same manner as in Example 1, except that the type of additive or the content of the additive was as shown in Table 1.

[0052] (evaluation) A bonded body was manufactured using the bonding paste obtained in each example. Specifically, a 3 mm opening was formed in an oxygen-free copper plate, and the bonding paste of each example was printed using a 50 μm-thick metal mask and metal squeegee, and then the plate was dried at 90°C for 5 minutes on a hot plate. A 2.5 mm x 2.5 mm silicon dummy chip with 100 nm-thick gold sputtered on the back side was placed on the plate, and the plate was heated at 250°C for 3 minutes while applying a pressure of 5 MPa in a nitrogen atmosphere to bond the plate. In the evaluation, the shear strength of the resulting bonded body (bonded silicon dummy chip and oxygen-free copper plate) was measured. A shear strength of 40 MPa was rated "excellent," 20 MPa or more but less than 40 MPa was rated "good," 10 MPa or more but less than 20 MPa was rated "passable," and less than 10 MPa was rated "unacceptable." "Fair," "Good," and "Excellent" were rated as passing. The shear strength of the obtained joint was measured by a method conforming to JIS Z 3198-7 (Lead-free solder test method - Part 7: Shear test method for solder joints of chip components). Specifically, a load was applied to the silicon dummy chip using a tool of a bond tester (Nordson DAGE, SERIES 4000), and the load (maximum shear load) when the silicon dummy chip peeled off from the copper joint layer was measured. The moving speed of the tool was 50 μm / sec, and the gap between the tip of the tool and the oxygen-free copper substrate was 50 μm. The obtained maximum shear load was converted into Newton and divided by the area (2.5 mm × 2.5 mm) of the copper joint layer to obtain the shear strength (unit: MPa). Seven joints were produced, and the shear strength of each joint was measured. The values ​​shown in Table 1 are the average shear strengths of the seven joints.

[0053] [Table 1]

[0054] Table 1 shows the evaluation results of each example. As shown in Table 1, the shear strength was acceptable in the examples, and it is understood that by using a joining paste containing 0.5% to 3.0% by mass of phosphate ester, it is possible to suppress the decrease in strength even when joining is performed in a non-reducing atmosphere. On the other hand, in Comparative Example 1 in which no phosphate ester was used as an additive, the shear strength was unacceptable, and it is understood that the decrease in strength cannot be suppressed when joining is performed in a non-reducing atmosphere. Also, in Comparative Examples 2 and 3 in which the content of phosphate ester is outside the range of 0.5% to 3.0%, the shear strength was unacceptable, and it is understood that the decrease in strength cannot be suppressed when joining is performed in a non-reducing atmosphere.

[0055] Although the embodiment of the present invention has been described above, the embodiment is not limited to the contents of this embodiment. The above-mentioned components include those that a person skilled in the art can easily imagine, those that are substantially the same, and those that are within the so-called equivalent range. Furthermore, the above-mentioned components can be appropriately combined. Furthermore, various omissions, substitutions, or modifications of the components can be made without departing from the gist of the above-mentioned embodiment. [Explanation of symbols]

[0056] 10 Bonding paste 12 Copper particles 14 Solvents 16 Additives 20 Bonding layer 21 First Component 22 Second member 30 zygote

Claims

1. A bonding paste comprising copper particles, a solvent, and an additive made of a phosphoric ester, A bonding paste, wherein the content of the additive is 0.5% or more and 3.0% or less by mass ratio with respect to the entire bonding paste, and the average molecular weight of the phosphate ester is 1,000 or more and 2,000 or less.

2. The bonding paste according to claim 1 , wherein a content of the solvent is 5% or more and 20% or less by mass ratio with respect to the entire bonding paste.

3. The bonding paste according to claim 1 or 2, wherein the surfaces of the copper particles are covered with an organic protective film.

4. The bonding paste according to claim 1 , wherein the copper particles have a BET diameter of 50 nm or more and 300 nm or less.

5. A method for producing a bonded body, comprising: bonding a first member and a second member together using the bonding paste according to claim 1 as a bonding layer to produce a bonded body.

Citation Information

Patent Citations

  • Power module, substrate therefor and method for manufacturing the both

    JP2004172378A

  • Pasty metal particulate composition, method for manufacturing solid metal or solid metal alloy, method for joining metallic members, method for manufacturing print wire board, and method for manufacturing bump for connecting electric circuits

    JP2014111800A

  • Copper fine particle dispersion liquid, conductive film forming method, and circuit board

    JP2014225338A

  • Joining material and joining method using same

    JP2018059192A

  • Conductor forming composition, and bonding body and method for producing the same

    JP2019067515A